A multiple case study on living room furniture considerations among selected Filipino middle class families - Santiago, Alaina C. (College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT The objective of this research is to determine the considerations made by selected middle class Filipino Families when acquiring living room furniture pieces in the context of intrinsic or extrinsic attributes under which the acquired furniture pieces fall. Intrinsic cues in the study are categorized into two aspects namely, form and function. Form covers the physical and aesthetic characteristics of the furniture pieces, while function pertains to their performance and utilitarian value. Price, brand, store image, and country of origin are specifically categorized as the extrinsic attributes included in the study. This is a multiple case which used description in analyzing gathered data. It included research techniques such as photo documentation, observation and interview. Three (3) respondents from three (3) dwelling types namely single-detached house, apartment or condominium and townhouse were chosen thru snowball sampling. A total of nine (9) living rooms of the chosen respondents were visited, analyzed and photo documented. Interviews were conducted by the researcher to reveal the actual experience of the respondents when acquiring living room furniture pieces. The results of the study provide insights on furniture acquisition preferences of the selected Filipino middle class with different dwelling types. The key findings show that intrinsic attributes play a significant role in furniture purchasing decision more than the extrinsic attributes. The data gathered indicate that the acquired furniture pieces of the families are mostly purchased by them. The common sources of these acquisitions are furniture stores, department stores, auctions, gifts from relatives and garage sales. It is recommended that future similar studies include a wider range or respondents across socio-economic classes.